DESIGNING LEARNING MEDIA FOR BATAKNESE CUISINE USING MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) METHOD - Tony Wibowo; Vincent Limken (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2021)
Learning media are generally defined as tools, methods, and techniques that are used sequentially to channel messages and learning information so that communication and interaction between lecturers and students can be more effective in the process of education and teaching. With the advancement of technology, learning media are no longer limited in form and number and can be easily used in the teaching process. Thus, learning media is an important part of the education process, and is one aspect that must be mastered by each teacher to be able to carry out its professional functions. The purpose of this research is to design a learning media for Bataknese Cuisine using Multimedia Development Life Cycle (MDLC) method. The result of this study is Bataknese Cuisine learning application developed and built using Unity software. This application design is expected to provide information and teach the user about Bataknese Cuisine.